THE IMPACT OF ONLINE GAME ADDICTION ON LEARNING ENTHUSIASM TO PROMOTE THE STUDENTS’ MOTIVATION TO LEARN - Winda Agustini; Marleni Marleni (Esteem Journal of English Education Study Programme, 2023)
The main purpose of this study is to examine the influence of online game addiction on the learning motivation of fourth-grade children. Specifically, the research focuses on investigating the impact of online game addiction on the enthusiasm for learning among fourth graders at SDN 1 Bubusan. The study involves fourth-grade students, class teachers, and parents of students who are addicted to online games at the mentioned school. A descriptive-qualitative research method is employed, and data collection techniques include observations, interviews, and questionnaires. Classroom sessions were observed to witness teachers delivering learning materials, and interviews were conducted with students, parents, and class teachers. Additionally, students completed questionnaires to gather their perspectives. Data analysis consisted of data reduction, data presentation, and drawing conclusions. The findings of this study reveal that online game addiction among children has a detrimental impact on their enthusiasm for learning. It leads to decreased motivation to study and a lack of attentiveness towards teachers' explanations of learning materials.